PENGARUH KUALITAS PELAYANAN, REPUTASI PERUSAHAAN DAN PROMOSI TERHADAP KEPUTUSAN PENGAMBILAN KREDIT MULTIPRODUK (Studi Kasus Pada PT. Astra Multi Finance “SPEKTRA” Semarang) - Ariya Pradipta; Naili Farida; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2015)
Financing Institution was a non-bank finance institution that provides a credit service for items or goods. This research was located in PT. Astra Multi Finance Semarang. The growth of the multiproduct credit in PT. Astra Multi Finance Semarang distributed since 2009 until 2013 was always increase in demand for credit. The increasing number of the credit growth was not equipoised by the number of complaints in PT. Astra Multi Finance Semarang which always increase. The number of complaints was increased since 2009 until 2013. The type of this research was Explanatory Research. The population of this research was the customers of PT. Astra Multi Finance Semarang which took the multiproduct credit with 100 people as the sample. The sampling method used in this research was Accidental Sampling while interview and questionnaires method were used as the techniques in collecting the data. The techniques used in processing the data were validity test, reliability test, a simple linear regression, multiple linear regression, hypothesis test using the (t test and F test) and the coefficient of determination which were done by using the SPSS 17 for Windows computer programs. Based on the analysis results, it can be concluded that there were any positive and significant influences between the service quality and the decision for taking the credit, between the company reputation and the decision for taking the credit, between the promotion and the decision for taking the credit, between the service quality, company reputation, as well as the promotion and the decision for taking the credit. The suggestions proposed were that the company should improve the employee ability in understanding the customer’s needs and improve the service pace of credit application process on PT. Astra Multi Finance Semarang. In additions, the company is expected to improve quality of the company itself, especially for the quality of the Human Resources in PT. Astra Multi Finance Semarang, and improve the advertising activity, especially for the design of advertisement as well as improving the variety of the promotion, so the information of the products can be understood and accepted by the general public.